TEACHING CLASSICAL LANGUAGES WITH DIRECT METHODS: UKRAINIAN ASPECT - Дорош, Марко; Галицька, Тетяна (Taras Shevchenko National University of Kyiv (Ukraine), 2021)
The article is dedicated to an overview of the prospects to introduce living (direct, immersive) methods in the teaching of Latin and Ancient Greek in Ukraine. Today, most teachers carry out the educational process using the principle of legere et intellegere (read and understand), while abroad in the second half of the previous century classical languages began to be learned implying living language methods. They include not only reading and translating texts, but also the ability to communicate and write in Latin and Ancient Greek. The presented study was conducted according to three criteria: feasibility, supply, and demand. Regarding the first criterion, the authors analyzed the existing foreign practices and identified the key examples of the involvement of such methods in teaching and independent learning of classical languages. A brief overview of the most popular schools was made and several projects that proved their worth abroad were singled out. Moreover, the current state of language teaching in Ukraine was considered upon the example of a private conversational club, YouTube channel, and a course in a higher education institution. They all combine living language methods with traditional ones. The authors interviewed representatives of each organization about their methodology, specifics of work, and target audience. Particular attention was paid to the place and method of direct classical languages study, especially taking into account the specifics of Ukraine. It was concluded that private institutions are more efficient than public ones. Regarding demand, it was found that the studied languages are becoming increasingly popular with contemporary society, so the potential audience is quite broad. It is also confirmed by the number of participants in researched Ukrainian educational projects. As a result of the study, the authors concluded on the prospects for the introduction of direct or combined methods in teaching Ancient Greek and Latin in the Ukrainian education system.

Присвячена огляду перспектив упровадження живомовних (прямих, імерсивних) методик у викладання латинської та да-вньогрецької мов в Україні. Натепер більшість викладачів здійснює освітній процес за принципом legere et intellegere (читати і розуміти), у той час як закордоном із другої половини минулого століття почали вивчати класичні мови із застосуванням живомовних методів. Вони передбачають не лише читання і переклад текстів, але і вміння спілкуватися й писати латинською та давньогрецької мовами. Представлене дослідження проведене за трьома критеріями: доцільність, наявність пропозиції і наявність попиту. Відносно першого критерію, автори проаналізували існуючі закордонні практики і виділили основні приклади залучення таких методик у викладання та самостійне вивчення класичних мов. Було зроблено короткий огляд найбільш популярних шкіл та виокремлено ряд проєктів, які довели свою доцільність закордоном. Більш того, було розглянуто актуальний стан живомовного викладання в Україні на прикладі приватного розмовного клубу, YouTube-каналу та курсу в державному закладі вищої освіти. Усі вони комбінують живомовні методи із традиційними. Автори проінтерв'ювали представників кожної організації стосовно їхніх методів, специфіки роботи та цільової аудиторії. Окрему увагу було приділено місцю і способу живомовного вивчення класичних мов, особливо з урахуванням української специфіки. Зроблено висновок щодо більшої ефективності приватних закладів, ніж державних ЗВО. Стосовно попиту виявлено, що досліджувані мови стають усе більш популярними в широких колах, тому потенційна аудиторія є досить великою. Це також підтверджується кількістю учасників розглянутих нами українських навчальних проєктів. Унаслідок дослідження автори зробили висновок щодо перспективності впровадження прямих чи комбінованих методик викладання давньогрецької та латинської мов в українську систему освіти.
ВИКЛАДАННЯ КЛАСИЧНИХ МОВ ЗА ЖИВОМОВНИМИ МЕТОДИКАМИ: УКРАЇНСЬКИЙ АСПЕКТ
Keywords: classical languages; direct teaching methods; higher educational institutions; language clubs; prospects of implementation; класичні мови; прямі методики викладання; ЗВО; мовні клуби; перспективи впровадження